An abyss where darkness dwells. (2nd November 2012) - Heimonen, Kirsi
This article enquires into the nature of the communication between a dance artist and people living with memory loss, brain damage and behavioural disorders. Art in this context means that something happens in the nursing community; its range travels from performances to dancing or gardening together. The core of the writing lies in the happenings that are discussed in the phenomenological and autoethnographic field. The article illuminates how something happens between a dance artist and the residents, something that happens in art, and through art, that can be described as an abyss where darkness dwells, a no-man's-land where nobody knows anything better than another. The happenings are discussed with texts by Georges Bataille and Emmanuel Levinas. The collision of the art happenings in the community also reveals some attitudes and habits of the nursing staff.